2022
DOI: 10.3389/fpsyg.2022.972556
|View full text |Cite
|
Sign up to set email alerts
|

A survey of college students’ willingness to participate in social practice with perceived environmental support based on the applied mixed research method

Abstract: Contemporary social reform promotes rapid social transformation, and social practice has a special educational function in higher education. However, research shows weak willingness to participate in social practice among college students. Using the mixed research method, 438 completed questionnaire surveys on perceived environmental support were collected from college students. The influence of perceived environmental support on Chinese college students’ willingness to participate in social practice was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Views and satisfaction of the participants of the meeting process as measured through validated tool Bélisle et al (2022); Niederman et al (2008) demonstrated SVC meetings can further reiterate the importance of these applied activities as contributing to the larger picture of social practice in educational institutions (Li et al, 2022).…”
Section: Validation Through Participant Views and Satisfactionmentioning
confidence: 93%
See 4 more Smart Citations
“…Views and satisfaction of the participants of the meeting process as measured through validated tool Bélisle et al (2022); Niederman et al (2008) demonstrated SVC meetings can further reiterate the importance of these applied activities as contributing to the larger picture of social practice in educational institutions (Li et al, 2022).…”
Section: Validation Through Participant Views and Satisfactionmentioning
confidence: 93%
“…In this work, student feedback that is communicated efficiently, well-received and accordingly acted upon; have impacted the overall constructive discourse during the meetings (Kauffeld and Lehmann-Willenbrock, 2012;Kauffeld and Meyers, 2009b;Lehmann-Willenbrock et al, 2017). Staff facilitators and educators, therefore, have pivotal role to play in developing student leaders and enhancing their participation in social practice (Allen and Lehmann-Willenbrock, 2023;Kauffeld and Lehmann-Willenbrock, 2012;Kauffeld and Meyers, 2009b;Lehmann-Willenbrock et al, 2011;Li et al 2022;Serriere et al, 2011;Zijlstra et al, 2012). It is important to note that student representatives in their role during SVC meetings, also communicate to student union within the wider teaching and learning communities.…”
Section: Educator Role and Social Practice Enhancementmentioning
confidence: 99%
See 3 more Smart Citations